Developing a framework to revolutionise the 4D BIM process: IPD-based solution - Elghaish, Faris; Abrishami, Sepehr (Construction innovation, 2020)
Purpose The integration of building information modelling (BIM) and integrated project delivery (IPD) is highly recommended for better project delivery. Although there is a methodology for this integration, the BIM requires some improvements to foster the adoption of IPD. The purpose of this paper is to present an innovative way to support 4D BIM automation/optimisation within the IPD approach. Similar to structural and architectural design libraries, this research proposes a planning library to enable automating the formulation of schedule, as well as embedding the multi-objective optimisation into the 4D BIM. Design/methodology/approach The literature review was used to highlight the existing attempts to support the automation process for 4D BIM and the multi-objective schedule optimisation for construction projects. A case study was done to validate the developed framework and measure its applicability. Findings The results show that there is a cost-saving of 22.86 per cent because of using the proposed automated multi-objective optimisation. The case study shows the significance of integrating activity-based costing into 4D BIM to configure the hierarchy level of overhead activities with the IPD approach; therefore, the maximum level of contribution in managing the IPD project is 33.33 per cent by the trade package level and the minimum contribution is around 8.33 per cent by the project level. Originality/value This research presents a new philosophy to develop the 4D BIM model – planning and scheduling – a BIM library of the project activities is developed to enable the automation of the creation of the project schedule with respect to the 3D BIM design sequence. The optimisation of the project duration is considered to be automated within the creation process by using the proposed genetic algorithm model.